Effect of chronic potassium loading on potassium secretion by the pars recta or descending limb of the juxtamedullary nephron in the rat. - Battilana, C A (1978)
Recently we demonstrated potassium secretion by the pars recta or by the descending limb of the juxtamedullary nephron. The purpose of this present investigation is to study the effect of a chronic high-potassium intake on this phenomenon. Fractional reabsorption of water and sodium by the juxtamedullary proximal nephron was decreased when compared to that in normal hydropenic rats. There was a striking increase in the fraction of filtered potassium at the end of the juxtamedullary descending limb from 94+/11% to 180+/18%, which was principally a result of enhanced potassium secretion. When the concentration of potassium in the collecting tubule fluid of potassium-loaded rats was reduced after the administration of amiloride, a sharp fall was observed in the amount of potassium which reached the end of the descending limb (64+/8%). A direct correlation was observed between the fraction of filtered potassium at the descending limb and the potassium concentration in the final urine (P less than 0.001). The findings suggest that potassium, like urea, normally undergoes medullary recycling, which is enhanced by chronic potassium loading.